2022
DOI: 10.1161/jaha.121.023152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Postoperative Atrial Fibrillation in Patients With Hypertrophic Cardiomyopathy Undergoing Septal Myectomy

Abstract: Background Obesity is an established cardiovascular risk factor in patients with hypertrophic cardiomyopathy. Postoperative atrial fibrillation (POAF) is one of the most common complications after surgery in patients with obstructive hypertrophic cardiomyopathy (OHCM). We aimed to determine the impact of body mass index (BMI) on the occurrence of POAF in patients with OHCM who underwent septal myectomy. Methods and Results In all, 712 OHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The results of our previous study demonstrated that age and BMI are independent risk factors for perioperative AF in patients with HCM [34], suggesting that HRV may play a role in the development of AF through age and BMI. Moreover, LAD was positively correlated with the rMSSD (p < 0.01) and pNN50 (p < 0.01), although the correlation between left atrial size and All rights reserved.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The results of our previous study demonstrated that age and BMI are independent risk factors for perioperative AF in patients with HCM [34], suggesting that HRV may play a role in the development of AF through age and BMI. Moreover, LAD was positively correlated with the rMSSD (p < 0.01) and pNN50 (p < 0.01), although the correlation between left atrial size and All rights reserved.…”
Section: Discussionmentioning
confidence: 85%
“…We also found a negative correlation between the SDNN and both age (p < 0.01) and BMI (p < 0.01), suggesting that total autonomic tone activity decreases with age and BMI. The results of our previous study demonstrated that age and BMI are independent risk factors for perioperative AF in patients with HCM [34], suggesting that HRV may play a role in the development of AF through age and BMI. Moreover, LAD was positively correlated with the rMSSD (p < 0.01) and pNN50 (p < 0.01), although the correlation between left atrial size and AF has been widely verified [35], suggesting that changes in parasympathetic nervous system tension may be associated with the occurrence of AF through changes in left atrial size.…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate the effects of lncRNA PVT1 on the recurrence of AF, the recurrence of AF was taken as the dependent variable, combined with the analysis results in Table 3 and the possible risk factors affecting AF previously reported 18–20 . Age, gender, HA, TGF‐β1, LAD, LVEDD, LAVI, LVRI, and lncRNA PVT1 were included in the binary logistic multivariate regression analysis model as independent variables.…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the effects of lncRNA PVT1 on the recurrence of AF, the recurrence of AF was taken as the dependent variable, combined with the analysis results in Table 3 and the possible risk factors affecting AF previously reported. [18][19][20] Age, gender, HA, TGF-β1, LAD, LVEDD, LAVI, LVRI, and lncRNA PVT1 were included in the binary logistic multivariate regression analysis model as independent variables. Multivariate logistic regression analysis demonstrated that after adjusting the sizes of LAVI and LVRI, and the level of TGF-β1, lncRNA PVT1 was the independent risk factor for postoperative recurrence of AF (p = 0.038, OR = 16.056, 95% CI: 1.170-220.359) (Tables 5 and 6).…”
Section: High Expression Of Lncrna Pvt1 Was An Independent Risk Facto...mentioning
confidence: 99%